2017
DOI: 10.1097/wnf.0000000000000245
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin Toxicity Manifesting as Reversible Encephalopathy With Continuous Triphasic Waves in Electroencephalogram

Abstract: A 74-year-old man with peripheral neuropathy due to diabetes presented with deliberate ingestion of 450 mg of pregabalin (PBG) over a period of 8 hours followed by altered mental status. A bedside electroencephalogram was performed to rule out nonconvulsive status epilepticus, which showed continuous triphasic waves (TWs) with slow background activity. He recovered after 48 hours of stopping PBG, and his repeat electroencephalogram after 72 hours did not show any TWs. We present a rare case of PBG-induced TWs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…These changes were attributed to the direct effect of PGB on the brain. These results were similar to previous reports of PGB causing encephalopathy and EEG changes [18][19][20].…”
Section: Discussionsupporting
confidence: 93%
“…These changes were attributed to the direct effect of PGB on the brain. These results were similar to previous reports of PGB causing encephalopathy and EEG changes [18][19][20].…”
Section: Discussionsupporting
confidence: 93%
“…Further, hepatotoxicity induced by pregabalin use was also suggested in the literature (11). In a study conducted in 2017 by Parekh et al (12), pregabalin overuse was reported to cause transient encephalopathy, together with continuous triphasic waves in electroencephalogram.…”
Section: Discussionmentioning
confidence: 89%
“…9 PGB-induced seizures respond well to stopping the drug and supportive measures. 17 However, prolonged encephalopathy up to 48 hours post-PGB-induced seizures has been reported. 8 Tapentadol is a synthetic mu-receptor agonist with 2-3 times lower affinity compared to morphine, but with additional noradrenaline (norepinephrine) reuptake inhibition within the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…PGB‐induced delirium, in older patients with multiple medical comorbidity and concurrent medications, is well reported; however, it may occur in young patients too 9 . PGB‐induced seizures respond well to stopping the drug and supportive measures 17 . However, prolonged encephalopathy up to 48 hours post‐PGB‐induced seizures has been reported 8…”
Section: Discussionmentioning
confidence: 99%